On WS Closed and WS Open Maps in Topological Spaces - A Sajjanar, Veeresha; M. Ittanagi, Basavaraj (International Journal of Engineering and Technology, 2018)
New type of closed and open maps called ws-closed and ws-open maps in topological spaces are introduced and studied. During this process some of their properties have been investigated. Also we introduce ws*-closed and ws*-open maps in topological spaces and discuss some properties.Â Â